2001
DOI: 10.1111/j.1469-7793.2001.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of rat central inhibitory synapses through GABA metabolism

Abstract: The brain adapts to experience by changing synaptic efficacy. Extensively studied mechanisms of plasticity include changes in the probability of transmitter release and in postsynaptic responsiveness. However, evidence from aminergic synapses indicates that the biochemistry of neurotransmitters provides an additional tool to alter synaptic strength. For example, dopaminergic transmission can be boosted by the precursor L-DOPA, which enhances the transmitter content of individual vesicles (Pothos et al. 1996) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 36 publications
7
79
1
2
Order By: Relevance
“…Several different mechanisms may explain this apparent discrepancy: presynaptic GABA receptors may be differentially expressed in different preparations and, most importantly, chloride extrusion mechanisms may differ [21]. There are also several experimental differences between the work by Engel et al [9] and our present approach, most notably the time of incubation. Indeed, the acute and long-term effects of vigabatrin may differ, causing even pro-convulsant effects of this anticonvulsant drug at early stages after application [22].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Several different mechanisms may explain this apparent discrepancy: presynaptic GABA receptors may be differentially expressed in different preparations and, most importantly, chloride extrusion mechanisms may differ [21]. There are also several experimental differences between the work by Engel et al [9] and our present approach, most notably the time of incubation. Indeed, the acute and long-term effects of vigabatrin may differ, causing even pro-convulsant effects of this anticonvulsant drug at early stages after application [22].…”
Section: Discussioncontrasting
confidence: 51%
“…5), vigabatrin suppressed both stimulus-evoked and miniature IPSCs. In a previous study, however, we had found an increased, rather than decreased, frequency of mIPSCs in cultured hippocampal slices after long-term incubation with vigabatrin [9]. Several different mechanisms may explain this apparent discrepancy: presynaptic GABA receptors may be differentially expressed in different preparations and, most importantly, chloride extrusion mechanisms may differ [21].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The latter can be achieved by scaling the amount of vesicular transporter protein per vesicle, which increases or decreases the vesicular loading capacity and thereby regulates the quantal size of transmitter release (Wilson et al, 2005). Alterations in the cytoplasmic levels of glutamate and GABA available for vesicular sequestration also result in corresponding changes in vesicular storage and release (Engel et al, 2001;Yamashita et al, 2003). The set point of synaptic vesicle glutamate and GABA storage might therefore be controlled by the number of functional transporters and the cytoplasmic transmitter concentration (Wilson et al, 2005) similarly to that described for the vesicular acetylcholine transporter after heterologous gene expression Erickson, 1996, 1997), supporting a steady-state equilibrium model of vesicle transmitter packet size (Williams, 1997).…”
Section: Scaling Of Vesicular Glutamate and Gaba Transporter Expressionmentioning
confidence: 99%
“…At central glutamatergic and GABAergic terminals, synaptic vesicles may not be filled to their maximal capacity (Engel et al, 2001;Yamashita et al, 2003), and release from single vesicles is not enough to saturate postsynaptic receptors at some synapses (Liu et al, 1999;Hajos et al, 2000;McAllister and Stevens, 2000;Ishikawa et al, 2002). Therefore, variability in the amount of transmitter loaded into vesicles at central excitatory and inhibitory synapses could significantly contribute to endogenous variations in quantal release measured in cultured neurons (Frerking et al, 1995;Liu et al, 1999) and in synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%